Effects of added elastic tubes on open-chain knee extensor strength training - de Oliveira Melo, M.; Brodt, G. A.; Gomes, L. E.; Tarrago Candotti, C.; La Torre, M.; Fagundes Loss, J. (Sports Biomechanics, 2013)
Attaching elastic tubes (ETs) to resistance training machines can affect the exercise load profile. The purpose of this study was to assess the training effects of added ETs, which were strategically attached to provide additional loads only during the deceleration phase of the knee extension exercise. Twenty-two healthy participants, assigned to either an experimental group (with ETs) or a control group (without ETs), participated in a 12-week strength-training program using a knee extension exercise machine. The acceleration effects were quantified and a method of attaching the ETs to the knee extension machine was developed. The effects of the added ETs were analysed by testing dynamic and isometric maximum contractions at four knee flexion angles (10°, 30°, 50°, and 80°). Analyses of covariance with the initial values as the covariate were used to examine the ET effects. A greater increase in isometric maximum strength was found in the experimental group than in the control group at knee flexion angles of 10° [effect size (ES) = 2.25] and 30° (ES = 1.18). No significant difference in the dynamic maximum strength was found between the groups. The use of ETs increased strength at smaller knee flexion angles with quadriceps that were relatively short.